2006
DOI: 10.1007/s00125-006-0333-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diabetes mellitus on cognitive decline in the oldest of the old: a prospective population-based study

Abstract: Aims/hypothesis Diabetes mellitus is a risk factor for the development of cognitive impairment and dementia in the general population up to 75 years of age. As part of the Leiden 85-plus Study we studied the effects of diabetes on cognition in the oldest old. Subjects and methods The Leiden 85-plus Study is a prospective population-based study of 599 persons from age 85 onward. Cognitive function was assessed each year from ages 85 to 90 by means of four neuropsychological tests. The presence of diabetes and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 42 publications
(53 reference statements)
9
79
0
5
Order By: Relevance
“…In a recent longitudinal study, with 4 years follow-up, we observed no accelerated decline in a well controlled T2DM group relative to controls [35]. Other longitudinal studies, that generally used relatively brief cognitive assessment batteries, also reported no or limited (up to 50% on top of the rate of normal aging) accelerated cognitive decline in individuals with T2DM [36][37][38].…”
Section: Cognition In Non-demented Individuals With T2dmmentioning
confidence: 64%
“…In a recent longitudinal study, with 4 years follow-up, we observed no accelerated decline in a well controlled T2DM group relative to controls [35]. Other longitudinal studies, that generally used relatively brief cognitive assessment batteries, also reported no or limited (up to 50% on top of the rate of normal aging) accelerated cognitive decline in individuals with T2DM [36][37][38].…”
Section: Cognition In Non-demented Individuals With T2dmmentioning
confidence: 64%
“…Participants were classified as having diabetes according to previously described criteria. 21 Information on smoking was obtained from questionnaires. Body mass index was calculated by dividing the weight in kilograms by the square of length in meters (kg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following older adults with and without type 2 diabetes over a 5-year period, van den Berg and associates (present issue of Diabetologia) [39] failed to find a faster rate of cognitive deterioration in diabetic patients over time, although at baseline (age: 85 years), diabetic patients performed more slowly on several speed tests, but this was largely attributable to their history of macrovascular disease (stroke). A greater degree of learning and memory dysfunction, generally considered to be a predictor of progression to dementia [40], was also not evident within the diabetic group.…”
Section: Absence Of Progressive Neurocognitive Deterioration In Oldermentioning
confidence: 93%